تقويم كتاب "دروس اللغة العربية" للأستاذ إمام زركشي والأستاذ إمام شباني - Abdullah Ubaid (Lugawiyyat, 2020)
The textbook has important role in the teaching and learning process. But, thetextbook has shortage and can mislead who learn this book if not prepared properly. Andthis phenomenon make evaluation of the textbook has important role in the teaching andlearning process.And the researcher found that some modern boarding school has been using thisbook "Durus al-Lughah al-Arabiyah" wich written by K.H. Imam Zarkasyi and K.H. ImamSubani. With this, the researcher want to do research about evaluation of the textbook"Durus al-Lughah al-Arabiyah" that used in modern boarding school Darussalam GontorPonorogo. And the researcher want to know the suitability of this book with the basicsof writing a good textbook in terms of the appearance and contents. And the approachused by the researchers is quantitative approach.After the researcher describe the data and then analyze it, the researcher foundsome result of this research about evaluation of the textbook "Durus al-Lughah al-Arabiyah",while the results are as follows: 1) In terms of appearance, the textbook "Durusal-Lughoh al-Arabiyah" has reached a good value. 2) In terms of content, the textbook"Durus al-Lughah al-Arabiyah" has reached a good value. However, this textbook is stillin need of improvement in terms of the appearance and the content, so that it can reachto the excellent value.